PROFIL TANIN PADA TEH SEDUH DENGAN PAPARAN SUHU PENYEDUHAN YANG BERBEDA - Diah Ariana; Nastiti Kartikorini; Siti Mardiyah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2021)
Abstract   Tea is a beverage widely consumed by all levels of society as in addition to economic and easy to get, tea is also deemed to provide health benefits. One of the compounds that plays a role as antioxidant and antimicrobial in the tea for body health is tannin. The size of tannin content received by body depends on the way of processing tea before drinking. The higher the infusion temperature of tea infusion, it will make the content of tannin in the drinks is increasing.   So the statement of problem in this research is whether there is any effect of infusion temperature on tannin content in tea infusion. This research aims to find out the effect of infusion temperature on tannin content in tea infusion.   The type is experimental research. The sample is infused tea mostly consumed by people which is sold in market of Pacar Keling Surabaya. Total of samples used in this research is 40 grams of infused tea packages divided into two (2) treatments with 8 repetitions in each treatment. The variables are independent variable namely infusion temperature while the dependent variable is tannin content.   From the examination of tannin content based on infusion temperature, it is known that the average of tannin content with infusion temperature of 700C and 1000C is 42.84% and 43.41% in a gram unit or 100 grams of infused water. The result of paired t test shows there is no effect of infusion temperature on tannin content in infusion tea with significant value more than 0.05 or 5%. Possible factor of no influence of temperature on tannin content is the length of infusion used which shall be not too long around 3-5 minutes. Password: Tea, Infusion Temperature, Tannin